Assessing the Partai Amanat Nasional (PAN) Solidity in Merangin Regency during the 2024 Regional Elections - Agus Dewi Susilo Wati; Dimas Subekti; Ian Pasaribu; Sutri Destemi Elsi (Jurnal Studi Ilmu Sosial dan Politik, 2026)
Purpose: This study examines the level of internal solidity of the Partai Amanat Nasional (PAN) in Merangin Regency in the context of the 2024 Simultaneous Regional Head Election. Methods: This research used qualitative methods with a case study approach. Data were collected through in-depth interviews with party elites, local party administrators, legislative members, political observers, and academics, complemented by document analysis of party statutes and bylaws, official party decisions, local media coverage, and electoral data provided by the General Election Commission. Results: The findings indicate that PAN Merangin demonstrated functional solidity, reflected in cadre loyalty, short-term organizational stability, and the absence of open internal fragmentation. However, this condition cannot yet be categorized as an institutionalized solidity. Decision-making remains highly centralized, formal conflict resolution mechanisms are weak, and cadre regeneration is not systematically institutionalized. Conclusions: The Partai Amanat Nasional (PAN) in Merangin Regency for the 2024 Simultaneous Regional Elections cannot be categorized as institutionally solid, although cadre loyalty is the cornerstone. Limitations: This study’s limitation is that it focuses only on the dynamics of PAN Merangin's solidity in the context of the 2024 simultaneous regional head elections, thereby limiting the generalizability of the findings to other parties or regions. Contributions: This study contributes to political science and local democracy studies by highlighting the gap between functional solidity and institutional strength within local political parties during regional electoral competitions.